Bioaccessibility and bioavailability of bioactive compounds from yellow mustard flour and milk whey fermented with lactic acid bacteria. Issue 22 (28th October 2021) - Escrivá, L.; Manyes, L.; Vila-Donat, P.; Font, G.; Meca, G.; Lozano, M.
Abstract : Lactic acid bacteria fermentation enriched ingredients in bioactive compounds. Yellow mustard flour and milk whey are potential natural preservative ingredients to be used in the baking industry, especially when fermented with lactic acid bacteria. Abstract : Microbial fermentation with lactic acid bacteria (LAB) is a natural food biopreservation method. Yellow mustard and milk whey are optimum substrates for LAB fermentation. The aim of the present study was to evaluate the bioaccessibility and bioavailability of bioactive compounds from yellow mustard flour and milk whey both with and without LAB fermentation. All extracts were subjected to a simulated digestion process. Total polyphenols, dl -3-phenyllactic acid (PLA), lactic acid, and the antioxidant activity were determined in the studied matrices before and after simulated digestion. Yellow mustard flour was significantly richer in total polyphenols, whereas significantly higher concentrations of PLA and lactic acid were observed in milk whey. Similar antioxidant activity was determined in both ingredients being in all cases strongly reduced after in vitro digestion. Higher bioaccessibility was found for polyphenols and PLA in milk whey. Transepithelial transport of total polyphenols was higher in yellow mustard flour compared to milk whey, reaching bioavailability values between 3–7% and 1–2%, respectively. PLA transepithelial transport was only significant in both fermented matrices with bioavailability around 4–6%. Transepithelial transport of lactic acid reached values of 31–34% (bioavailability ∼ 22%) and 15–78% (bioavailability ∼ 3%) in milk whey and yellow mustard flour, respectively. LAB fermentation showed beneficial effects on enriching extracts with PLA, lactic acid, and antioxidant activity, as well as increasing bioaccessibility of these acids in yellow mustard flour and total polyphenol bioavailability in milk whey. Results pointed to yellow mustard flour and milk whey as natural preservative ingredients used in the food industry, especially when fermented with LAB.